The Army's Role in Overcoming Anti-Access and Area Denial Challenges - Gordon IV, John; Matsumura, John (RAND Corporation, 2023)
The U.S. armed forces must be prepared to deploy to a wide range of locations and confront adversaries that span the threat spectrum. This report reviews selected findings from a study of Army and joint anti-access and area denial challenges and proposes a joint approach to countering these threats in future operations.